E-books in university libraries: resources, services and 20 key areas for development - Merlo-Vega, José-Antonio (Anuario ThinkEPI, 2015)
This article describes the current e-books situation in Spanish university libraries, analyzing their distribution and access models. The five stages of an e-book library service are described: selection, acquisition, processing, access and evaluation. The specific aspects that should be taken into account in each phase are explained, and illustrated with some examples.
Keywords: Electronic books; Ebooks; University libraries; Electronic information; Digital resources; Library services; Scientific publishing; Digital loan.